Postural characterization in visually impaired young adults: preliminary study - Tavares, Graziela Morgana Silva; Santo, Caroline Cunha do Espírito; Libardoni, Thiele de Cássia; Santos, Cristina Maria; Nunes, Paula Martins; Sinhorim, Larissa; Mota, Daniel Henrique; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The postural control system, responsible for maintaining the erect posture, is a strongly influenced by the visual system. Posture is the state of balance between muscles and bones, capable of protecting other structures of the human body from possible injuries. The visual system plays an important role in stabilizing the posture by continuously provide, with respect to the current position and the segments of the body in relation to themselves and the environment information nervous system. Objective: Characterize postural profile of young adults with visual impairment using computerized photogrammetry. Methods: A postural analysis was performed in thirteen subjects 8 female and 5 male (30.85 ± 6.85 years), by recording images of the anterior, posterior and lateral views. All data were analyzed using the SAPO postural assessment software and the results tabulated in Microsoft Office Excel 2007 program. Descriptive statistics were performed. Results: It was shown that the subjects in this study had the following changes in postural profile: forward head, torso leaning back, pelvic anteversion and valgus hindfoot. Conclusion: The findings of this study showed that the attitude of these individuals is characterized by forward head, posterior tilt of the trunk, anterior pelvic tilt, knees flexed and valgus hindfoot. Additionally, it appears that this quantitative and qualitative method, low cost, can easily be incorporated into the clinical setting, it is useful to health professionals in the identification of postural changes and consequently the most appropriate treatment for these individuals.